Implementasi Teknik Kursi Kosong Dalam Meningkatkan Kestabilan Emosional Siswa Korban Bullying Dilingkungan Santri - Nadia Sahnura; Wanty Khaira (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
This study aims to analyze the effectiveness of the Empty Chair Technique in improving the emotional stability of students who are victims of bullying at MTsS Ulumul Qur’an Banda Aceh. The research used a quantitative experimental approach with a one-group pretest–posttest design and involved four students selected through purposive sampling based on indications of having experienced bullying. Data were collected through questionnaires and observations, then analyzed using the Shapiro–Wilk normality test and paired sample t-test. The treatment was carried out in three individual counseling sessions lasting 35 minutes each. The results showed a 25% decrease in emotional instability scores after applying the Empty Chair Technique, indicating an improvement in emotional control and self-awareness. Statistical analysis revealed a significant difference between pretest and posttest scores (p < 0.05). Thus, the Empty Chair Technique effectively helps students externalize negative emotions, reduce anxiety, and achieve emotional balance